Diffuse lymphadenitis and disseminated Mycobacterium avium subsp. paratuberculosis infection in two wild Eurasian otters (Lutra lutra L. 1758) - Matos, A.C. (2016)
Diffuse lymphadenitis and disseminated Mycobacterium avium subsp. paratuberculosis infection in two wild Eurasian otters (Lutra lutra L. 1758).